The use of a mixture of somatic and culture filtrate antigens in the evaluation of the immune response to Paracoccidioides brasiliensis - Silva, M. I. Correa da; Carvalho, I. Maximo de; Franco, T. N.; Cunha, M. A.; Chamma, L. G.; Fogaca, J.; Fecchio, Denise [UNESP]; Franco, M. (Blackwell Science, 1991)
Three Paracoccidioides brasiliensis antigens, namely a culture filtrate preparation, a somatic antigen and a mixture of equal parts of the two, were tested by two serological techniques against sera from patients with paracoccidioidomycosis, and in an in vivo delayed hypersensitivity model in mice. The antigen mixture was more sensitive than the two individual antigens for the evaluation of humoral and cellular immune response to P. brasiliensis, both in man and in experimental animals.
Keywords: Antigen; Vaccine; Animal cell; Animal tissue; Controlled study; Culture medium; Human; Human tissue; Immune response; Major clinical study; Mouse; Nonhuman; Paracoccidioides brasiliensis; Patient; Serum; Animal; Antibodies, Fungal; Antigens, Fungal; Enzyme-Linked Immunosorbent Assay; Human; Hypersensitivity, Delayed; Immunodiffusion; Mice; Paracoccidioides; Paracoccidioidomycosis; Sensitivity and Specificity; Animalia; Paracoccidioides brasiliensis; paracoccidioidomycosis brasiliensis